Effect Of Liquidity, Profitability, Company Size, and Leverage On Profit Quality In Sub-Sector Manufacturing Companies Automotive Period 2018-2022 - Falah, Zulfa Azni; Ajun Nurul Afa; Gunawan Aji; Al Hayu Lestari; Riska Ayu Andini (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this study was to determine the effect of liquidity, profitability, firm size, and leverage on earnings quality. This type of research is a qualitative research with a literature review study approach The population of this study is made up of manufacturing firms in the automobile subsector that are listed on the Indonesia Stock Exchange for the years 2018 through 2022. The results show that liquidity, profitability, and firm size have a significant effect on earnings quality. While leverage has no effect on eamings quality.